2018
DOI: 10.1111/jace.16244
|View full text |Cite
|
Sign up to set email alerts
|

Bi0.5K0.5TiO3–CaTiO3 ceramics: Appearance of the pseudocubic structure and ferroelectric‐relaxor transition characters

Abstract: In this study, solid solution ceramics of (1−x)Bi0.5K0.5TiO3–xCaTiO3 (BKT‐CT, x = 0, 0.12, 0.15, 0.18, 0.21, and 0.25) were prepared. A phase transition from the tetragonal symmetry to the pseudocubic symmetry is discovered near x = 0.25. The reasons for the appearance of the pseudocubic phase were discussed. The compositions of x ≤ 0.21 show the ferroelectric ordering at room temperature. The remnant polarization (Pr) is 22.4 μC/cm2 for the x = 0.15 composition. The temperature dependence of the relative perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…The RFE states of BKT-D1 and BT-D2 can be identified by the board peak in the dielectric spectrum, with the diffuseness parameter γ being 1.82 and 1.92 (Figure S4), respectively. A significant frequency-dependent dielectric maximum is observed, with Δ T max being 90 K for BKT-D1, and 70 K for BT-D2, indicating the presence of small size and weakly coupled polar nanoregions. , These relaxor features will be beneficial to the high-field energy storage performance.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The RFE states of BKT-D1 and BT-D2 can be identified by the board peak in the dielectric spectrum, with the diffuseness parameter γ being 1.82 and 1.92 (Figure S4), respectively. A significant frequency-dependent dielectric maximum is observed, with Δ T max being 90 K for BKT-D1, and 70 K for BT-D2, indicating the presence of small size and weakly coupled polar nanoregions. , These relaxor features will be beneficial to the high-field energy storage performance.…”
Section: Resultsmentioning
confidence: 95%
“…A significant frequency-dependent dielectric maximum is observed, with ΔT max being 90 K for BKT-D1, and 70 K for BT-D2, indicating the presence of small size and weakly coupled polar nanoregions. 43,44 These relaxor features will be beneficial to the high-field energy storage performance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should be noted that this electric field of relaxor to ferroelectric phase transition is larger than the reported BNT-based ergodic phase that can induced long-range ferroelectric domain. 45 The large P 2 of 0.1CBTZ indicates a harder field -induced phase transition from relaxor to ferroelectric phase. In contrast, the electric field of P 1 decreases from 15 kV/cm to close to 0 kV/cm for x = 0.06 and 0.1, indicating an easier recovery of ferroelectric phase.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman modes below ~ 150 cm −1 are related to the Bi 3+ vibrations [36]. The Raman modes between 200 -380 cm −1 are thought to be contributed by the Ti-O vibration [15,44]. Raman modes between 500 -650 cm −1 are dominated by Ti-O 6 octahedral vibrations [44,45].…”
Section: Phase Evolution and Raman Analysismentioning
confidence: 99%
“…The BKT is a perovskite ferroelectric material with a relatively higher Curie temperature (T c = 380°C) [10][11][12] than other perovskite-based materials such as BNT and BT [13]. Furthermore, BKT is one of the rare lead-free perovskites which crystallizes in a tetragonal symmetry at room temperature (RT) [14,15], while most of others are in rhombohedral phase. It has been reported that BKT can potentially form a rhombohedral-tetragonal MPB with many other leadfree compositions [13].…”
Section: Introductionmentioning
confidence: 99%